Coupled mechanical oscillator enables precise detection of nanowire flexural vibrations - Maneesha Sharma; Aniruddha Sathyadharma Prasad; Norbert H. Freitag; Bernd Büchner; Thomas Mühl (Communications Physics)
Abstract The field of nanowire (NW) technology represents an exciting and steadily growing research area with applications in ultra-sensitive mass and force sensing. Existing detection methods for NW deflection and oscillation include optical and field emission approaches. However, they are challenging for detecting small diameter NWs because of the heating produced by the laser beam and the impact of the high electric field. Alternatively, the deflection of a NW can be detected indirectly by co-resonantly coupling the NW to a cantilever and measuring it using a scanning probe microscope. Here, we prove experimentally that co-resonantly coupled devices are sensitive to small force derivatives similar to standalone NWs. We detect force derivatives as small as 10−9 N/m with a bandwidth of 1 Hz at room temperature. Furthermore, the measured hybrid vibration modes show clear signatures of avoided crossing. The detection technique presented in this work verifies a major step in boosting NW-based force and mass sensing.